Zero-sum : stories - Oates, Joyce Carol, 1938- (Alfred A. Knopf, 2023)
"A brilliant young philosophy student bent on seducing her famous philosopher-mentor finds herself outmaneuvered; diabolically clever high school girls wreak a particularly apt sort of vengeance on sexual predators in their community; a man returns from the dead to haunt his grieving wife; a young mother finds herself captivated by her own motherhood. In the collection's longest story, a much-praised writer cruelly experiments with "drafts" of his own suicide. In these powerfully wrought stories that hold a mirror up to our time, Joyce Carol Oates has created a world of erotic obsession, thwarted idealism, and ever-shifting identities. Provocative and stunning, Zero Sum reinforces Oates's standing as a literary treasure and an artist of the mysterious interior life"--